AN IMPROVED RESOURCE ALLOCATION STRATEGY BASED ON PACKAGE LEVEL ACCESS IN CLOUD ENVIRONMENT - Kaur, Rajveer; Ghumman, Mr. Navtej Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Cloud computing is an emerging field of computer science, where heterogeneous services such as applications, servers and storage are delivered to an individual or organization's computer and devices through the Internet. In the proposed research work, a load balancing algorithm is designed, to provide proper utilization of all resources while processing the requests received from the users. We have implemented the ‘package’ level access at the Virtual Machines. We have proposed three types of packages like basic, medium and premium according to the requirements of the Cloudlets. In the basic package, we have the Virtual Machines with low capacity and in the premium package we are having the Virtual Machines with higher capacity, whereas the medium is of intermediate capacity of MIPS and RAM. In the proposed approach, the capacity, status and current load of every Virtual Machine is computed before allocating the new request of the user. Different parameters like waiting time, execution time and turnaround time of the Cloudlets are computed and analyzed. The proposed research provides the anticipated results with the implementation of the proposed algorithm. Compared with the other job scheduling algorithms, the proposed load balancing algorithm can outperform them in circumstances where the load and Virtual Machines are heterogeneous.